Cannabinoid modulation of alpha2 adrenergic receptor function in rodent medial prefrontal cortex. (18th August 2014) - Cathel, Alessandra M.; Reyes, Beverly A. S.; Wang, Qin; Palma, Jonathan; Mackie, Kenneth; Van Bockstaele, Elisabeth J.; Kirby, Lynn G.
Abstract Endocannabinoids acting at the cannabinoid type 1 receptor (CB1R) are known to regulate attention, cognition and mood. Previous studies have shown that, in the rat medial prefrontal cortex (mPFC), CB1R agonists increase norepinephrine release, an effect that may be attributed, in part, to CB1Rs localised to noradrenergic axon terminals. The present study was aimed at further characterising functional interactions between CB1R and adrenergic receptor (AR) systems in the mPFC using in vitro intracellular electrophysiology and high‐resolution neuroanatomical techniques. Whole‐cell patch‐clamp recordings of layer V/VI cortical pyramidal neurons in rats revealed that both acute and chronic treatment with the synthetic CB1R agonist WIN 55, 212‐2 blocked elevations in cortical pyramidal cell excitability and increases in input resistance evoked by the α2‐adrenergic receptor (α2‐AR) agonist clonidine, suggesting a desensitisation of α2‐ARs. These CB1R–α2‐AR interactions were further shown to be both action potential‐ and gamma‐aminobutyric acid‐independent. To better define sites of cannabinoid–AR interactions, we localised α2A‐adrenergic receptors (α2A‐ARs) in a genetically modified mouse that expressed a hemoagglutinin (HA) tag downstream of the α2A‐AR promoter. Light and electron microscopy indicated that HA‐α2A‐AR was distributed in axon terminals and somatodendritic processes especially in layer V of the mPFC. Triple‐labeling immunocytochemistry revealed that α2A‐AR and CB1R were localised to processes that contained dopamine‐β‐hydroxylase, a marker of norepinephrine. Furthermore, HA‐α2A‐AR was localised to processes that were directly apposed to CB1R. These findings suggest multiple sites of interaction between cortical cannabinoid–adrenergic systems that may contribute to understanding the effect of cannabinoids on executive functions and mood.